Energy policy regime change and advanced energy storage: A comparative analysis. (April 2018) - Winfield, Mark; Shokrzadeh, Shahab; Jones, Adam
Abstract: This paper employs a multi-level perspective approach to examine the development of policy frameworks around energy storage technologies. The paper focuses on the emerging encounter between existing social, technological, regulatory, and institutional regimes in electricity systems in Canada, the United States, and the European Union, and the niche level development of advanced energy storage technologies. The structure of electricity systems as vertically integrated monopolies, or liberalized or semi-liberalized markets, is found to provide different mechanisms for niche formation and niche to regime transition pathways for energy storage. Significant trade-offs among these pathways are identified. The overwhelming bulk of energy storage policy development activities are found to be taking place in liberalized or semi-liberalized markets. The key policy debates in these markets relate to technical barriers to market participation by storage resources, the ability of storage technologies to offer multiple services in markets simultaneously, the lack of clear rules related to the aggregation of distributed energy resources, and issues related to the meaning of "technological neutrality" in liberalized market systems. Landscape conditions, particularly jurisdictional commitments to pursue deliberate reconfigurations of their energy systems towards low-carbon energy sources, emerge as the most significant factor in the implementation of policy reforms in these areas. Highlights: Storage is an enabling technology which may disrupt conventional utility models. Private capital is increasingly interested in storage technology development. The strengths of liberalized markets for new technologies are also their weaknesses. The existing rules present barriers to full utilization of energy storage technologies. The low-carbon reconfiguration of energy systems will define the role of storage.